A detailed modelling on spray atomisation and combustion of LOX/GCH4 in variable area pintle injector rocket engines. Issue 4 (7th June 2021) - Radhakrishnan, Kanmaniraja; Lee, Keonwoong; Koo, Jaye
Abstract : The spray combustion of LOX/GCH4 in the pintle injector is simulated to study the combustion characteristics at a subcritical condition by considering the effects of pintle opening distance and pintle tip angle. To perform the simulation, first, the VOF simulation was used to estimate the LOX sheet thickness and breakup length. Second, the breakup constants for the secondary breakup model were calculated using the results of VOF and the Lagrangian approach was used to estimate the Sauter mean diameter around the injector exit. Finally, the spray combustion of LOX/GCH4 simulation was performed using the estimated SMDs data. Subsequently, the spray combustion characteristics were discussed by considering the individual effects of pintle opening distance at fixed pintle tip angle, and pintle tip angle at fixed pintle opening distance using various contours such as temperature, mass fraction of OH, and discrete phase model evaporation of LOX droplets. Following this, the characteristic velocity and combustion efficiency were shown for various cases. The optimised design of the pintle injector based on the simulated results was summarised for future liquid rocket pintle injectors.